PENINGKATAN MOTIVASI BELAJAR BAHASA INGGRIS MELALUI PENDEKATAN PENGEMBANGAN MASYARAKAT YANG KREATIF DAN BERBASIS ASET - Shalihah, Imra'atus; Balqis, Rizqiyah Ratu; Permatasari, Yovita Dyah; Maghfiroh, Naily Inayatul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service project was conducted at SMK Al-Qodiri 2, a vocational school under a pesantren (Islamic boarding school) that has an active language community outside formal class. The program aimed to enhance students’ English proficiency and learning motivation through the implementation of the Asset-Based Community Development (ABCD) approach combined with creative teaching methods. This approach focuses on empowering existing community assets such as students’ enthusiasm, teacher support, and the pesantren’s culture of collaboration. The four-week program consisted of eight interactive sessions employing educational games, music, and group discussions. The results indicated a significant improvement in vocabulary mastery, speaking skills, and students’ self-confidence. The average English proficiency score increased from 45% to 74%, while learning motivation rose from 50% to 83%. Furthermore, the program encouraged the sustainability of the school’s language community through initiatives such as the English Corner. Therefore, the combination of the ABCD approach and creative learning methods proved effective in improving students’ English abilities and fostering an active learning culture within the pesantren environment.